Analysis of brain and muscle activity during low‐level tooth clenching – a feasibility study with a novel biting device. (7th January 2014) - Iida, T.; Overgaard, A.; Komiyama, O.; Weibull, A.; Baad‐Hansen, L.; Kawara, M.; Sundgren, P. C.; List, T.; Svensson, P.
Summary In electromyographic (EMG) and functional magnetic resonance imaging (fMRI) studies, muscle and brain activity was compared during low levels of tooth clenching using a novel biting device to control bite force. A total of 21 healthy subjects performed motor tasks, comprising tooth clenching at 5, 10 and 20 N. During all measurements, subjects kept the novel bite device between the anterior teeth during tooth clenching. The EMG study (n = 15) characterised jaw muscle activity for the three motor tasks and demonstrated significant differences in root mean square (RMS) EMG amplitude between 5‐, 10‐ and 20‐N tooth clenching (F = 46·21, P < 0·001). There were no differences in variability of muscle activity between the three tooth‐clenching levels. In an fMRI pilot study (n = 6), statistical comparisons were used to identify brain regions with significant activation in the subtraction of baseline from 5‐ or 20‐N tooth‐clenching activity. 5‐ and 20‐N tooth clenching significantly and bilaterally activated the sensorimotor cortex, supplementary motor area, cerebellum and basal ganglia (P < 0·05, corrected for multiple comparisons). However, activation of each brain region did not differ significantly between two tooth‐clenching tasks. Based on these preliminary findings, we propose that the novel biting device may be useful in further fMRI studies on controlled jaw muscle activation patterns in different craniofacial pain conditions. In addition, our fMRI result suggests that there are no significant differences in brain activity within low levels of tooth clenching with controlled force.